Single and Competitive Sorption of Heavy Metal Ions (Cd2+ & Cu2+) on a Clayey Soil - Vibhawari; N. D. Pandey (E-Journal of Chemistry)
The present paper focuses on the sorption behavior of Cd2+ ion on clayey soil at different initial concentration at natural soil pH and sorption of Cd2+ ion in the presence of Cu2+ ion (competitive-ion solution) on clayey soil at different initial concentrations at the same soil pH. Sorption experiments were carried out for the agitation period of 1 to 10 days. It was observed that in both the cases concentration of both the metals remaining in the solution with the agitation time was non linear. Maximum adsorption capacities of Cd2+ ion in both the solutions were calculated. It was observed that sorption of Cd2+ ion was decreased in the presence of Cu2+ ion. It was concluded that as a result of competition of ions, sorption of Cd2+ decreased.